Radio Suara Surabaya's Marketing Communication Strategy In Seeking Advertising Clients - Anwar, Miftahol; Nada, LIfatin; Zain, Feri; Amin, Mohammad (Manunggal Halim Jaya, 2025)
Competition among radio stations is becoming increasingly fierce due to the increasing number of radio stations. For private radio stations, advertising is a key input in operating as a professional and profitable mass media outlet. Therefore, radio stations must have a marketing communications strategy to attract advertisers. The author chose Radio Suara Surabaya as the research object because, amidst intense competition in the Indonesian broadcast radio industry for advertisers, Radio Suara Surabaya remains viable and resilient. The research question is how Radio Suara Surabaya employs its marketing communications strategy to attract advertisers. The purpose of this research is to determine Radio Suara Surabaya's marketing communications strategy. This qualitative study used primary data collection through observation, interviews, and documentation. The results concluded that Radio Suara Surabaya's marketing communications strategy to attract advertisers focuses heavily on a personal and integrated approach, based on SWOT and STP analyses. Radio SS employs a compelling promotional mix of personal selling, advertising, and public relations, which has proven to be superior in terms of app installs and followers across various social media platforms.